Ayurvedic Management of Secondary Infertility Due to Polycystic Ovarian Syndrome - A Case Report - Anila, M; Parvathy, S (International Research Journal of Ayurveda & Yoga, 2022)
Polycystic Ovarian Syndrome is an endocrinological disorder which is common among women of reproductive age. It is the main cause of anovulatory infertility. The main features of PCOS are oligovulation/anovulation, Hyperandrogenism, menstrual irregularities, infertility, insulin resistance, obesity. In Ayurveda symptoms of PCOS are often met in nashtartava, artavakshaya, anapatyata, sthoulya, prameha. Here we report a case of secondary infertility due to PCOS. She was obese and her cycles were anovulatory with heavy bleeding. The patient underwent Panchakarmanusara shodana chikitsa in Govt Ayurveda college hospital, Thiruvanathapuram. The treatment aimed to correct agnimandya, control heavy bleeding, and regularize menstrual cycle. She conceived after treatment and delivered a healthy baby through LSCS.